1996
DOI: 10.1111/j.1432-1033.1996.0229t.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies of the Free α Subunit of Human Chorionic Gonadotropin

Abstract: Human chorionic gonadotropin (hCG) is a heterodimeric glycoprotein hormone that is involved in the maintenance of the corpus luteum in early pregnancy. Glycosylation at Am52 of its a subunit (ahCG) is essential for signal transduction, whereas the N-glycan at Am78 stabilizes the structure of the protein.In this study, an almost complete 'H-NMR and a partial "C-NMR spectral assignment for the amino acids and the N-glycans of ahCG and of an enzymatically deglycosylated form, which had a single GlcNAc residue at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 77 publications
5
59
0
Order By: Relevance
“…Here, the R-helix changes partly to a 3-helix or turn motif (Figure 10). The main effect that can be seen from the data is that removal of the first R-helix (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] destabilizes the second R-helix (amino acids [23][24][25][26][27][28][29][30][31][32] in its relative position and also in its fold, as revealed from the analysis of the secondary structure ( Figure 10). This finding is not an artifact of superimposing residues 40-120 for the rmsd analysis: using all backbone atoms for superimposition gives the same result.…”
Section: Bs In Solventmentioning
confidence: 99%
“…Here, the R-helix changes partly to a 3-helix or turn motif (Figure 10). The main effect that can be seen from the data is that removal of the first R-helix (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] destabilizes the second R-helix (amino acids [23][24][25][26][27][28][29][30][31][32] in its relative position and also in its fold, as revealed from the analysis of the secondary structure ( Figure 10). This finding is not an artifact of superimposing residues 40-120 for the rmsd analysis: using all backbone atoms for superimposition gives the same result.…”
Section: Bs In Solventmentioning
confidence: 99%
“…This showed that the location of the added cysteines made a difference in their ability to inhibit binding of the latch disulfide to either cysteine 26 or ␣-subunit S43C, revealing that the location of ␣-subunit loop 2, adjacent to the ␤-subunit, is most likely to be in the position occupied in Fig. 3 (D-F) as opposed to being disordered as observed during NMR analysis of hCG ␣-subunit loop 2 (28). The reason for this is that one ␤-subunit cysteine substitution (F64C) had a roughly equal ability to latch its seatbelt to ␤-subunit cysteine 26.…”
Section: Discussionmentioning
confidence: 93%
“…Based on the data in Table 4, it is clear that the ␣-subunit is already attached to the ␤-subunit in a position where both the ␣-and ␤-subunit cysteine knots are proximal to one another. This would permit ␣-subunit loop 2, which has been shown to be disordered in the free subunit (28), to be in the vicinity of these ␤-subunit residues as well as the ␤-subunit tail. In our model, the position of the ␣-subunit hydrophobic residues in loop 2 would allow for the migration of the hydrophobic ␤-subunit tail away from the seatbelt, enabling it to become latched to the cysteine at position 26.…”
Section: Discussionmentioning
confidence: 99%
“…substitution of cysteines for ␣Pro38 and ␣Pro40). Because the conformation of ␣-subunit loop 2 in the free ␣-subunit is known to be highly disordered (28), this observation suggested that docking of the subunits may stabilize the conformation of ␣-subunit loop 2 to one that is roughly similar to the conformation seen in the native heterodimer.…”
Section: Figmentioning
confidence: 88%